Analysis of Strategies for Handling Non-Performing Financing in Rahn Products at KSPPS BMT Mandiri Sejahtera, Dukun Branch - Alda Naila Adibah; M. Lutfillah Habibi, SEI, MSA, (Management and Education Journal, 2025)
This study aims to analyze the strategy for handling non-performing financing (NPF) in Rahn (Islamic pawn) products at KSPPS BMT Mandiri Sejahtera, Dukun Branch, East Java. The research employs a qualitative descriptive approach using interviews, observations, and documentation. The results reveal that problematic financing is mainly caused by internal and external factors, such as weak initial analysis, unstable economic conditions, and member negligence. The handling strategies include a systematic process of warnings, direct visits, formal notices, rescheduling, collateral sales, and PPAP. Moreover, a personal approach based on silaturahmi and the absence of additional margins reflect the application of justice and Islamic principles in maintaining financing quality.